Invasive lobular carcinomas of the breast--the prognosis of histopathological subtypes. - du Toit, R. S. (Nature Publishing Group, 1989)
One hundred and seventy-one cases of operable invasive lobular carcinoma, presenting over an 11-year period, were reviewed. Histological subtypes were investigated to determine differences in their clinical behaviour and whether these differences could be explained by histopathological features. Five subtypes were identified: mixed (45.6%), classical (30.4%), tubulo-lobular (13.5%), solid (6.4%) and alveolar (4.1%). The median follow-up period was 64 months and the median age 54 years. The 12-year actuarial survival rate was 100% for the tubulo-lobular subtype, but only 47% for the solid variant. Similar differences were found in the disease free interval, locoregional and distant metastatic rates between these two subtypes. The tubulo-lobular tumours were more likely to be of good histological grade and node negative. The other three subtypes did not differ significantly in their histopathological parameters, reflected in similar clinical behaviour. They occupied an intermediate position between the other two subtypes in terms of prognosis.